Population Growth Performance of Arma custos (Faricius) (Hemiptera: Pentatomidae) at Different Temperatures. Issue 5 (21st October 2022) - Wang, Jie; Mu, Yinlin; Yang, Can; Yang, Lin; Zhang, Changhua; Yu, Huiping; Chang, Zhimin; Long, Jiankun; Chen, Xiangsheng
Abstract: Arma custos (Fabricius) (Hemiptera: Pentatomidae) is a natural predator that can control various agricultural and forestry pests. This study aimed to clarify the effects of temperature on the growth, reproduction, and population of the predator and to simulate its population growth. Using the age–stage, two-sex life table method, 18°C, 22°C, 26°C, 30°C, and 34°C were selected as the temperature conditions. A. custos can complete its life cycle at 18°C–30°C, and the developmental duration of each A. custos stage, adult pre-oviposition period, total pre-oviposition period, and the mean generation time ( T ) were shortened with the increase in temperature. The pre-adult mortality was significantly reduced at 26°C and 30°C. In addition, the fecundity of a single female and the gross reproductive rate were the highest at 30°C. Significant differences were observed in the intrinsic rate of increase ( r ) and the finite rate of increase ( λ ) under different temperature conditions, and both reached the maximum at 30°C. Results showed that adult A. custos raised at 26°C had a longer lifespan and the fecundity was higher at 30°C in comparison with the other temperatures. This study is the first to report the life cycle of A. custos at different temperatures, and the results can provide a scientific theoretical basis for the indoor artificial reproduction, outdoor release, and colonization of A. custos .